Methodologies for measuring the quality of services applied to a university library - Cevallos Ampuero, Juan (2011)
The work has identified four dimensións related to service quality of the Library of the Universidad Nacional Mayor de San Marcos UNMSM. Three of them, which has been called “Tangible Aspects, Empathy and Reliability” can be considered equivalent to those originally obtained by Parasuraman, Zeithaml and Berry. The remaining dimensión is the integrated by Capacity of Response and Security has been called “Response-Security”. The dimensións found are consistent with the findings of other research in the university sector, but not included among those found by those authors. Also, has been tested the use of Neural Networks techniques and grouping with K Means, giving an equivalent result to factorial analysis. In the case of neural networks was used competitive learning with Learning Vector Quantitative LVQ.